Effect of training surface on acute physiological responses following sport-specific training - Binnie, M.; Peeling, P.; Pinnington, H.; Landers, G.; Dawson, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
This study compared the effect of sand and grass training surfaces during a sport-specific training session in well-trained team sport athletes (n=10). Participants initially completed a preliminary testing session to gather baseline (BASE) performance data for vertical jump (VJ), repeated sprint ability (RSA) and 3 km running time trial (RTT). Three days subsequent to BASE, all athletes completed the first sportspecific training session, which was followed by a repeat of the BASE performance tests the following day (24 h post-exercise). Seven days later, the same training session was completed on the opposing surface, and was again followed 24 h later by the BASE performance tests. During each session, blood lactate (BLa), ratings of perceived exertion (RPE) and heart rate (HR) were recorded, with player movement patterns also monitored via global positioning system (GPS) units. Additionally, venous blood was collected pre-, post-, and 24 h post-exercise, and analysed for serum concentrations of Myoglobin (Mb), Haptoglobin (Hp) and C-Reactive Protein (CRP). Results showed significantly higher HR and RPE responses on SAND (p>0.05), despite significantly lower distance and velocity outputs for the training session (p>0.05). There were no differences in 24 h post-exercise performance (p>0.05), and blood markers of muscle damage, inflammation and hemolysis were also similar between the surfaces (p>0.05). These results suggest that performing a sport-specific training session on a sand (versus grass) surface can result in a greater physiological response, without any additional decrement to next day performance